Konsep Maslahat dalam Menyikapi Masalah Kontemporer (Studi Komparatif al-Tûfi dan al-Ghazali) - Hermanto, Agus (al-'adalah, 2017)
The concept of maslahat offered by al-Ghazali is more general, compared to the concept offered by al-Tûfi. On the similarity side, both al-Ghazali and al-Tûfi alike have the principle that maslahat theory can be used as an Islamic law to address contemporary issues, although both develop this concept from the earlier scholars especially Imam Malik first pioneering. But both have different concepts, al-Ghazali emphasizes more on the criteria and definitions of the maslahat, both mu’tabarah, mulgha and mursalah, but al-Tûfi actually develops from maslahahmursalah, using much more reason and logic than al-Ghazali, even assumes that al-Tûfi seems strange compared to other figures and is considered inconsistent with his Hanbal school, nevertheless al-Tûfi remained confined to al-mu’âmalah and ‘âdat and not worship and muqaddarah territories.